An Adjusted Error Score Calculation for the Farnsworth-Munsell 100 Hue Test. Issue 2 (3rd July 2019) - Esposito, Tony
ABSTRACT: The Farnsworth-Munsell 100 Hue Test, a test that measures an individual's hue discrimination ability, operates with the fundamental assumption that it is administered using a fixed, standard illuminant. This assumption is violated when the testing illuminant is changed—as is common when testing color discrimination ability of an illuminant—which likely causes a reordering of the caps in the test. To ensure that a participant is not falsely penalized for correctly responding to a hue transposition caused by the new testing light source, an adjusted error score is proposed that reconciles light source–induced hue transpositions and participant performance on the test.